Botnet detection using automated script / Norfathin Rosli - Rosli, Norfathin (2020)
This paper is about a Botnet Detection using Automated Script, the programming language is and the operating system is Windows 7. The project is dedicated for Network and Security Analyst to develop better algorithm for botnet detect and prevents. This Botnet are malicious software that controlled networks of hijacked computers and aiming for distributed coordinate network initiate various malicious over network activities including click fraud, spam, and phishing. Nowadays, as we know the virus or malware spread can be so fast and usually hard to detect. This simulation is to detect the Botnet presence and identifying its behaviour. This project using Python script to kill the process of Botnet.